Horizon causality from holographic scattering in asymptotically dS3 - Victor Franken; Takato Mori (Journal of High Energy Physics)
Abstract In the AdS/CFT correspondence, a direct scattering in the bulk may not have a local boundary analog. A nonlocal implementation on the boundary requires O(1/G N ) mutual information. This statement is formalized by the connected wedge theorem, which can be proven using general relativity within AdS3 but also argued for using quantum information theory on the boundary, suggesting that the theorem applies to any holographic duality. We examine scattering within the static patch of asymptotically dS3 spacetime, which is conjectured to be described by a quantum theory on the stretched horizon in static patch holography. We show that causality on the horizon induced from null infinities I $$ \mathcal{I} $$ ± is consistent with the theorem. Specifically, signals propagating in the static patch are associated with local operators at I $$ \mathcal{I} $$ ± . Our results suggest a novel connection between static patch holography and the dS/CFT correspondence.